Effect of coitus at term on length of gestation, induction of labor, and mode of delivery. - Tan, Peng Chiong; Andi Asri, Andi Anggeriana; Mat Adenan, Noor Azmi; Mohd Nordin, Noraihan (Lippincott, Williams & Wilkins, 2006)
OBJECTIVE: To determine coital incidence at term and to estimate its effect on labor onset and mode of delivery.